Analisis Pengendalian Persediaan Bahan Baku dengan Menerapkan Metode EOQ (Economic Order Quantity) pada PT. Jatisari Furniture Work - Arga Sutrisna; Rizki Ginanjar; Suci Putri Lestari (Universitas Batanghari Jambi, 2021)
This research objectives aims to determine and analyze raw material inventory control, the ideal raw material inventory that the company must provide and the efficiency of production costs carried out by Jatisri Furniture Work in Tasikmalaya for the period 2018.11 – 2020.02. The data collection method in this study is by direct observation at Jatisari Furniture Work in Tasikmalaya. Using techniques such us interviews, observation, and documentation. These observations were made in production reports for the years 2018 – 2020. The analysis tool was carried out using the Economic Order Quantity (EOQ) method such us safety stock, reorder point, and total inventory cost. The result of the Economic Order Quantity (EOQ) analysis show that the total cost of raw the material inventory that must be incurred by the company is greater than the total cost of inventories calculated according to the EOQ method. Companies should follow the calculations from the EOQ method so that they can save on raw material inventory costs, so that production costs are more efficient.